Peningkatan Kesehatan Reproduksi Remaja melalui Pos Kesehatan Remaja di SMPN 1 Rancaekek dan SMA 5 Muhammadiyah Wilayah Puskesmas Rancaekek: Pos Kesehatan Remaja - Antri Ariani; Agung Sutriyawan; Iceu Mulyati; Ecih Winengsih; Tata Juarta (LPPM Akbid Harapan Ibu Pekalongan, 2024)
Adolescence is a period of rapid growth and development, both physically, psychologically and intellectually. Adolescent reproductive health problems include premarital sex, early marriage, early pregnancy, drugs, and HIV/AIDS. WHO (2015) states that around 21 million teenage girls become pregnant every year and almost half (49%) experience unwanted pregnancies. Another problem that affects adolescent health is anemia. According to WHO, the prevalence of anemia in Indonesian women is 23.9%, which has an impact on stunted physical growth, behavioral and emotional disorders, decreased productivity, impaired mental and intellectual development, as well as decreased body immunity and morbidity. Along with physical and psychological changes, teenagers must adapt to the changes that occur to them. During the menstrual period, the problem of dysmenorrhea appears, which has an impact on the daily activities carried out by teenagers at school. The Community Service that will be carried out is the Formation and Training of Adolescent Health Post Management (PoKeRja) and Providing Health Education to all students. The results of implementing this activity showed that before providing education, more than half had sufficient knowledge (53.8%) and after providing education, they had good knowledge (59.6%) regarding health in adolescents. The Adolescent Health Post has been established with support from partner schools SMA 5 Muhammadyah and SMPN 1 Rancaekek as well as students who are administrators of the adolescent health post at their school.